2015
DOI: 10.1155/2016/9392404
|View full text |Cite
|
Sign up to set email alerts
|

PAN‐811 Blocks Chemotherapy Drug‐Induced In Vitro Neurotoxicity, While Not Affecting Suppression of Cancer Cell Growth

Abstract: Chemotherapy often results in cognitive impairment, and no neuroprotective drug is now available. This study aimed to understand underlying neurotoxicological mechanisms of anticancer drugs and to evaluate neuroprotective effects of PAN-811. Primary neurons in different concentrations of antioxidants (AOs) were insulted for 3 days with methotrexate (MTX), 5-fluorouracil (5-FU), or cisplatin (CDDP) in the absence or presence of PAN-811·Cl·H2O. The effect of PAN-811 on the anticancer activity of tested drugs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Compared to in vivo studies, relatively few in vitro studies have investigated the direct effects of anticancer drugs on neurons [38][39][40]. In primary cultures of rat neural stem cells or progenitor cells and hippocampal neurons, cisplatin and temozolomide induced mitochondrial DNA damage, impaired respiratory activity, and increased oxidative stress [39,40].…”
Section: Neuronal and Glial Oxidative Stress Induced By Chemotherapeutic Drugs In Preclinical Studiesmentioning
confidence: 99%
“…Compared to in vivo studies, relatively few in vitro studies have investigated the direct effects of anticancer drugs on neurons [38][39][40]. In primary cultures of rat neural stem cells or progenitor cells and hippocampal neurons, cisplatin and temozolomide induced mitochondrial DNA damage, impaired respiratory activity, and increased oxidative stress [39,40].…”
Section: Neuronal and Glial Oxidative Stress Induced By Chemotherapeutic Drugs In Preclinical Studiesmentioning
confidence: 99%
“…Cisplatin-related side effects (ototoxicity, nephrotoxicity, neurotoxicity and cerebral disorders) limits its clinical use at the desired dosage [ 6 , 7 ]. Several studied have investigated the mechanisms of cisplatin toxicity but the mechanisms for induction of peripheral neuropathies is poorly understood [ 8 10 ]. One study showed the ability of cisplatin to penetrate into the brain where it inhibits neuronal stem cell proliferation [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both MTX and 5-FU can pass the blood-brain barrier (BBB) in amounts that are sufficient to cause cognitive impairment [ 2 , 9 11 ], possibly by increasing oxidative stress (OS) [ 10 , 12 , 13 ]. In line with this mechanism, we previously demonstrated that MTX/5-FU-induced in vitro neurotoxicity is OS-dependent [ 14 ]. Increased OS, which is associated with various forms of chemotherapy [ 10 ], can elicit apoptosis of primary neural precursor cells and reduce the number of proliferation cells in the hippocampus of rodents [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 82%
“…In the present study, PAN-811 fully preserved neurogenesis in the DG of hippocampus under MTX/5-FU insult. Since MTX/5-FU most likely damaged neurons by oxidative stress in the same way as it is toxic to cultured neurons [ 14 ], the preservation of these neurons by PAN-811 may be via suppression of MTX/5-FU-elicited oxidative stress. In support of this hypothesis, our previous study revealed that PAN-811 can inhibit ischemic or hypoxic neurotoxicity to post-mitotic neurons by scavenging free radicals and suppressing OS [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation